Know your neighbor : Jim Pappas (The Raton Daily Range Raton, New Mexico, 1964)
Newspaper Article on Jim Pappas and a bit of history from moving from Greece to the States and ending up in Raton, New Mexico.
Master list item #: 27
File location is in the Raton File Cabinet
Keywords: Pappas, Jim (Pappoedomanolakis, Demetros); Makris, Mike; Christos, Mike; Damengos, Pete; Petritis, Gus; Kintsel, Eric; Honeyfield, Marcum; Gust, Jim; Logan, Tom; Sillic, Mary; Pappas, Mike; Van Houten Coal Mining; Red Cross; Bisbee Pool Hall; TO Ranch; A.M. Van Dyke Ranch; Deluxe Bar; Gus' Malt Shop; Korner Kandy Kitchen; Kaufman's Jewelry Store; Sweet Shop; Local History; Biography; Life and Customs; Travel; Hard work; Coal Mining; Business Owner; Goat herd; Ranching; Cheese Business; Candy making; Name Change; Raton, New Mexico; Greece; New York City, New York; Van Houten, New Mexico; Waco, Texas; Springer, New Mexico; Denver, Colorado